Die Transformation des Kirchenbegriffs in der Frühaufklärung - Lehmann, Roland M. (Jus ecclesiasticum, 2013)
The concept of the church underwent a transformation in the early Enlightenment when two horizons were broadened, one beyond the boundaries of theology and one within them. As a result, the dogmatic concept of church expanded and ecclesiology was addressed outside of dogmatic theology.